Solve the following linear equation.
$ \frac{x}{2}-\frac{1}{5}=\frac{x}{3}+\frac{1}{4} $.


Given:

$\frac{x}{2}-\frac{1}{5}=\frac{x}{3}+\frac{1}{4}$.

To do:

We have to solve the given linear equation.

Solution:

$\frac{x}{2} - \frac{1}{5} = \frac{x}{3}+\frac{1}{4}$

This implies,

$\frac{x}{2} -\frac{x}{3} =\frac{1}{4} +\frac{1}{5}$

$\frac{3\times x-2\times x}{6}=\frac{1\times5+1\times4}{20}$

$\frac{3x-2x}{6}=\frac{5+4}{20}$

$\frac{x}{6}=\frac{9}{20}$

$x=6\times\frac{9}{20}$

$x=\frac{27}{10}$

The value of $x$ is $\frac{27}{10}$.

Updated on: 10-Oct-2022

33 Views

Kickstart Your Career

Get certified by completing the course

Get Started
Advertisements